PENGGUNAAN HOTPLATE SUHU 60°C SELAMA 10 MENIT SEBAGAI ALTERNATIF PEMANASAN PROSES FIKSASI SEDIAAN HISTOLOGI - Burhannudin Burhannudin; Warida Warida; Indah Puspita (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2023)
Background: The fixation process in histological preparation has been shortened by using microwave heating at 60°C for 2-10 minutes while maintaining the quality. However, the use of hotplates in this process is still limited. The study aims to determine the optimal duration of hotplate heating at 60°C for fixation. Method: An experimental study was conducted using a post-test-only control group design. The study includes 20 histological specimens from two control groups (conventional and microwave) and three treatment groups with hotplate heating durations of 3 minutes (W1), 5 minutes (W2) and 10 minutes (W3). Histological slides were evaluated based on staining results and scored using a scoring system (0-3). The scoring was tested using the Kruskal-Wallis and Mann-Whitney tests, with a significance level of p<0.05. Result: microscopic evaluation of the specimens revealed dark staining with Haematoxylin and Eosin in the W2 and W3 groups. However, the W1 group showed similar results (p>0.05) compared to the control group, while the W2 and W3 groups indicated significantly different results (p<0.05) compared to the control group. Conclusion: using a hotplate at 60°C for 10 minutes effectively accelerated the fixation process without compromising the quality of Haematoxylin and Eosin staining in histological specimens.